Estrategias de promoción a través del inbound marketing como aporte en el posicionamiento digital del sector gastronómico de la ciudad de Ambato - López Jijón, Ronald Jesús (2023)
The research project developed aims to analyze different success stories in the gastronomic sector of the city of Ambato and the digital marketing strategies implemented to achieve an exemplary positioning in social networks in order to identify and propose a strategic guide that contributes to the digital positioning of companies in the gastronomic sector in the city of Ambato. Increasingly, it has been noticed the increase of companies that migrate to social networks a large part of their advertising efforts. However, the lack of knowledge of content planning through strategies that work specifically for their sector has caused many of these companies to stop relying on the investment of targeted campaigns. For this, the analysis of the three best positioned companies was essential because, although they do not offer the same product to the market, they are in the same sector that seeks to satisfy basic consumer needs.